Heart health in Lebanon and considerations for addressing the burden of cardiovascular disease. Issue 3 (September 2015) - Deek, Hiba; Newton, Phillip; Inglis, Sally; Kabbani, Samer; Noureddine, Samar; Macdonald, Peter S.; Davidson, Patricia M.
Summary Introduction Lebanon is a small country located at the western boundary of the Middle East. Approximately 40% of health care in Lebanon is financed by the public sector. Cardiovascular diseases in Lebanon are scarcely addressed in the literature raising the need for baseline data on these health condition to be better treated. Aim To (1) aggregate and define the burden of cardiovascular disease in Lebanon and (2) describe implications for policy, practice and research to improve health outcomes in Lebanon. Method An integrative review was conducted of both peer-reviewed papers and unpublished reports. CINAHL, Medline, Google Scholar and Academic Search Complete were searched along with the websites of The World Health Organization, Ministry of Public Health Lebanon and Central Intelligence Agency of Lebanon. No year limit was applied to our search. Results The search yielded 28 peer-reviewed articles and 15 reports. Cardiovascular diseases are the leading cause of morbidity and mortality in Lebanon and is also the primary cause of hospital admission. A range of social, political, economic and cultural factors explain the burden of cardiovascular diseases, some of these risks are culture specific such as the arghile smoking and the high rates of familial hypercholesterolemia. Workforce shortage produced by high rates of migrating nurses also has an implication on the patients' outcomes. Conclusion Much of the presented data are sourced from the gray literature; more research, using systematic and prospective data collection methods, are needed to inform health services planning, delivery and evaluation. Primary care needs to be enhanced to produce better outcomes for a population with high profile of cardiovascular risk factors.